Hermeneutika Nasr Hamid Abu Zaid dan Muhammad Arkoun Dalam Memahami Kitab Turats Islam - Aulia Rahman; Muflihaini; Namlul Wadi; Rabbiyatul Saniah (Al-Ahnaf: Journal of Islamic Education, Learning and Religious Studies, 2025)
Hermeneutics is one of the methods for understanding texts. In its development, hermeneutics was also used in understanding the book of Turats Islamy. Some modern Islamic intellectuals tried to apply hermeneutics to Turats Islamy. Among these Muslim intellectuals were Nasr Hamid Abu Zaid and Muhammad Arkoun. The research method used in this article is qualitative research. Qualitative research methods are used because the purpose of this paper is interpretation. This research refers to the critical paradigm by originating from the hermeneutic understanding of Nasr Hamid Abu Zaid and Muhammad Arkoun in a descriptive form in the form of hermeneutic understanding in the Book of Turats Islamy. Research data were obtained from journals and other sources related to the hermeneutic thought of Nasr Hamid Abu Zaid and Muhammad Arkoun. The results of this research analysis prove that the hermeneutic thinking of Nasr Hamid Abu Zaid and Muhammad Arkoun is the same using history-based hermeneutics. Understanding the book of Islamic turats according to Nasr Hamid Abu Zaid and Muhammad Arkoun must understand the aspects and stages of history behind the book of turats.